A study to assess the self-care practices among hypertensive patients in a tertiary care center, Chennai - Sivakumar, Krithiga; Megavi Ramasamy; Mayadevi Thankayyan; Seenivasan P (Asian Journal of Medical Sciences, 2023)
Background: Hypertension is one of the important chronic diseases. Blood pressure (BP) control depends on adherence to self-care practices. Hence, the factors associated with poor adherence can help the policymakers in formulating and directing interventions at specific groups. Aims and Objectives: The current study was conducted to assess the self-care practices and to explore the factors associated with them. Materials and Methods: A cross-sectional study was conducted among 119 hypertensive patients who attended the outpatient department between July 2022 and September 2022 using a semi-structured interview schedule containing information on sociodemographic characteristics, morbidity profile, and self-care practices. Data were entered in MS Excel and analyzed using SPSS16. Chi-square test and Fisher’ exact test were used wherever appropriate. P<0.05 was considered statistically significant. Results: Among the study participants, 19.3% (23) had poor adherence to self-care practices and 80.7% (96) had good adherence to self-care practices (medication adherence=80.5%, regular monitoring of BP=89.1%, alcohol abstinence=94.1%, non-smoking=93.3%, diet modification=71.4%, and physical exercise=45.4%). Sociodemographic characteristics such as age, sex, occupation, education, family income, duration of hypertension, and place of purchase of medicine were found to be statistically significant to at least one of the recommended self-care practices. Conclusion: Overall adherence to self-care practices was found to be good in the majority of the study participants. Among the self-care practices, adherence to medication, monitoring BP, alcohol abstinence, non-smoking, and diet modification were found satisfactory (>70%). However, engagement in physical exercise still needs improvement. Health education and other interventions to promote physical exercise, especially among high-risk groups are suggested.